Improving household nutrition security and public health in the CARICOM, 2018-2022 - Waneisha Jones; Madhuvanti M. Murphy; Fitzroy Henry; Leith Dunn; T. Alafia Samuels (Pan American Health Organization, 2022)
The Caribbean is experiencing a worsening epidemic of obesity and noncommunicable diseases (NCDs) and it has the worst rates of premature mortality from cardiovascular diseases in the region of the Americas. Creating enabling environments to improve dietary diversity would help reduce obesity and diet-related NCDs. The Improving Household Nutrition Security and Public Health in the CARICOM project aimed to increase dietary diversity in the Caribbean, and to determine and implement effective, gender-sensitive interventions to improve food sovereignty, household food security, and nutrition in CARICOM states. Primary quantitative and qualitative research, scoping reviews, stakeholder engagement, implementation of interventions and dissemination activities were undertaken. This paper describes the overall project design and implementation, discusses challenges and limitations, and presents core achievements to inform further work in Small Island Developing States throughout CARICOM to advance the nutrition agenda in the Caribbean. The results of the project's research activities are presented in other papers published in this special issue on nutrition security in CARICOM states.